RECEPTION ANALYSIS OF FARMERS GROUP MEMBERS AGAINST AGRICULTURAL INTERACTIVE DIALOGUE BROADCAST PROGRAM AT PERSADA FM RADIO AND MAYANGKARA FM, JOINT EXECUTIVE AGENCY EXTENSION OF AGRICULTURE, FISHERIES AND FORESTRY (BP4K) BLITAR - Yefi Dyan Nofa Harumike (JARES (Journal of Academic Research and Sciences), 2017)
This research was conducted by the interest of the researcher looking at the active phenomenon of mass communication media in the community. The researcher chose to conduct a research on a broadcasting program of interactive dialogue organized by BP4K Blitar, because in previous studies regarding the reception of audience have never used the broadcast program audience interactive dialogue. This type of research is qualitative descriptive research using audience reception analysis is based on the concept of encoding/decoding stated Stuart Hall. The researcher compiled the study based on the theory models used to determine the audience reception of the broadcasting program of agricultural interactive dialogue with the theme of the broadcast organic mushroom cultivation timber Persada FM radio broadcast and organic fertilizer production Mayangkara FM radio broadcast. Reception results obtained from this study, both the theme of agriculture broadcast interactive dialogue on the theme of organic wood mushroom cultivation, as well as organic fertilizer there are three positions, namely dominant, negotiated and oppositional. In a dominant position audience is inclined to accept the message and then applied the same as those interpreted by a messenger, to the position negosiated audience besides receiving and applying the meaning of the message delivered with creators message yet been of meaning other than experience, while for the position of oppositional audiences tend to have a different meaning with delivering message, and the application also made on the basis of personal experiences and knowledge. Keywords: Agriculture interactive dialogue, Organic wood mushroom cultivation, Organic fertilizer Received: 6 August, 2017; Accepter: 10 September, 2017